1999
DOI: 10.1038/sj.onc.1202790
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-associated E-cadherin mutations alter cellular morphology, decrease cellular adhesion and increase cellular motility

Abstract: A major function of the cell-to-cell adhesion molecule Ecadherin is the maintenance of cell adhesion and tissue integrity. E-cadherin de®ciency in tumours leads to changes in cell morphology and motility, so that Ecadherin is considered to be a suppressor of invasion. In this study we investigated the functional consequences of three tumour-associated gene mutations that aect the extracellular portion of E-cadherin: in-frame deletions of exons 8 or 9 and a point mutation in exon 8, as they were found in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(147 citation statements)
references
References 75 publications
(59 reference statements)
7
137
0
3
Order By: Relevance
“…When E-cadherin cDNA with in-frame deletions of exons 8 or 9, or a point mutation in exon 9, were introduced into breast cancer cell lines, the cells adopted a more malignant, invasive and aggressive behaviour relative to those cells that were transfected with wild-type cDNA. 37 Such results suggest that our findings might indicate an association between the presence of E-cadherin mutations and the invasive behaviour of the studied tumours. However, we were unable to find any association between the presence of these mutations and altered prognosis (data not shown), which was not unexpected given the relatively small numbers of tumour samples involved.…”
Section: Mechanisms Of Loss Of Protein Expressionsupporting
confidence: 52%
“…When E-cadherin cDNA with in-frame deletions of exons 8 or 9, or a point mutation in exon 9, were introduced into breast cancer cell lines, the cells adopted a more malignant, invasive and aggressive behaviour relative to those cells that were transfected with wild-type cDNA. 37 Such results suggest that our findings might indicate an association between the presence of E-cadherin mutations and the invasive behaviour of the studied tumours. However, we were unable to find any association between the presence of these mutations and altered prognosis (data not shown), which was not unexpected given the relatively small numbers of tumour samples involved.…”
Section: Mechanisms Of Loss Of Protein Expressionsupporting
confidence: 52%
“…54 It has been suggested that mutation of exon 8 of CDH1 expresses an abnormal E-cadherin protein that lacks the appropriate signals for post-translational modifications, which permit the normal transport to the cell membrane and glycosylation of E-cadherin; this results in the arrest of E-cadherin in the Golgi apparatus. 53,55 In another report, cytoplasmic E-cadherin was present in a gastric adenocarcinoma with a 5-bp insertion in exon 9. 56 The significance of a lower aberrant p53 expression (39% vs 75%) in the two subclusters (cytoplasmic vs complete loss of E-cadherin) is unclear.…”
Section: Discussionmentioning
confidence: 94%
“…A major function of E-cadherin protein is the maintenance of cell adhesion and tissue integrity. E-cadherin deficiency in tumours would lead to changes in cell morphology and motility, so that E-cadherin is being considered to be a suppressor of cancer invasion [30]. In primary HCCs, E-cadherin expression is absent or reduced in amount as compared to normal liver tissues, which may be connected with intrahepatic metastasis of hepatocellular carcinoma [31], [32].…”
Section: Discussionmentioning
confidence: 99%